African swine fever virus (ASFV) protection mediated by NH/P68 and NH/P68 recombinant live-attenuated viruses. Issue 19 (3rd May 2018) - Gallardo, Carmina; Sánchez, Elena G.; Pérez-Núñez, Daniel; Nogal, Marisa; de León, Patricia; Carrascosa, Ángel L.; Nieto, Raquel; Soler, Alejandro; Arias, María Luisa; Revilla, Yolanda
Abstract: The risk of spread of African swine fever virus (ASFV) from Russia and Caucasian areas to several EU countries has recently emerged, making it imperative to improve our knowledge and defensive tools against this important pathogen. The ASFV genome encodes many genes which are not essential for virus replication but are known to control host immune evasion, such as NFκB and the NFAT regulator A238L, the apoptosis inhibitor A224L, the MHC-I antigen presenting modulator EP153R, and the A276R gene, involved in modulating type I IFN. These genes are hypothesized to be involved in virulence of the genotype I parental ASFV NH/P68. We here describe the generation of putative live attenuated vaccines (LAV) prototypes by constructing recombinant NH/P68 viruses lacking these specific genes and containing specific markers.